Integrating Deep Learning-based Instruction and Character Strengthening to Enhance Primary School Teachers’ Competence - Subowo Dikdayana Dikdayana (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Primary education plays a strategic role in shaping students’ foundational knowledge, attitudes, and character; therefore, the quality of instruction and teacher competence are key factors in improving educational outcomes. However, classroom practices remain largely dominated by surface learning approaches that emphasise memorisation and short-term cognitive achievement. Objective: This study aims to examine the relationship between deep learning–based instruction, character strengthening, and the enhancement of primary school teachers’ competence. Method: The study employs a qualitative approach through a literature review, using critical analysis and theoretical synthesis of various scholarly sources and educational policy documents. Result: The findings indicate that deep learning–based instruction can enhance conceptual understanding, higher-order thinking skills, and the internalisation of character values when supported by teachers’ pedagogical, professional, social, and personal competencies. Conclusion: Integrating these three aspects yields a holistic and sustainable learning framework that supports meaningful learning processes in primary education. Contribution: This research enriches theoretical perspectives on meaningful learning design by integrating character development with comprehensive teacher competence development.